Efficacy and safety of acupuncture-point stimulation combined with opioids for the treatment of moderate to severe cancer pain: a network meta-analysis of randomized controlled trials - Zhang, Qinglin; Yuan, Yuntong; Zhang, Meiling; Qiao, Baohua; Cui, Yiyuan; Wang, Ying; Feng, Li (Frontiers in Oncology, 2023)
Background Pain is one of the most common and troublesome symptoms of cancer. Although potential positive effects of acupuncture-point stimulation (APS) on cancer pain have been observed, knowledge regarding the selection of the optimal APS remains unclear because of a lack of evidence from head-to-head randomized controlled trials (RCTs). Objective This study aimed to carry out a network meta-analysis to compare the efficacy and safety of different APS combined with opioids in treating moderate to severe cancer pain and rank these methods for practical consideration. Methods A comprehensive search of eight electronic databases was conducted to obtain RCTs involving different APS combined with opioids for moderate to severe cancer pain. Data were screened and extracted independently using predesigned forms. The quality of RCTs was appraised with the Cochrane Collaboration risk-of-bias tool. The primary outcome was the total pain relief rate. Secondary outcomes were the total incidence of adverse reactions, the incidence of nausea and vomiting, and the incidence of constipation. We applied a frequentist, fixed-effect network meta-analysis model to pool effect sizes across trials using rate ratios (RR) with their 95% confidence intervals (CI). Network meta-analysis was performed using Stata/SE 16.0. Results We included 48 RCTs, which consisted of 4,026 patients, and investigated nine interventions. A network meta-analysis showed that a combination of APS and opioids was superior in relieving moderate to severe cancer pain and reducing the incidence of adverse reactions such as nausea, vomiting, and constipation compared to opioids alone. The ranking of total pain relief rates was as follows: fire needle (surface under the cumulative ranking curve (SUCRA) = 91.1%), body acupuncture (SUCRA = 85.0%), point embedding (SUCRA = 67.7%), auricular acupuncture (SUCRA = 53.8%), moxibustion (SUCRA = 41.9%), transcutaneous electrical acupoint stimulation (TEAS) (SUCRA = 39.0%), electroacupuncture (SUCRA = 37.4%), and wrist–ankle acupuncture (SUCRA = 34.1%). The ranking of total incidence of adverse reactions was as follows: auricular acupuncture (SUCRA = 23.3%), electroacupuncture (SUCRA = 25.1%), fire needle (SUCRA = 27.2%), point embedding (SUCRA = 42.6%), moxibustion (SUCRA = 48.2%), body acupuncture (SUCRA = 49.8%), wrist–ankle acupuncture (SUCRA = 57.8%), TEAS (SUCRA = 76.3%), and opioids alone (SUCRA = 99.7%). Conclusions APS seemed to be effective in relieving cancer pain and reducing opioid-related adverse reactions. Fire needle combined with opioids may be a promising intervention to reduce moderate to severe cancer pain as well as reduce opioid-related adverse reactions. However, the evidence was not conclusive. More high-quality trials investigating the stability of evidence levels of different interventions on cancer pain must be conducted. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/#searchadvanced, identifier CRD42022362054.